PENGARUH JARAK CELAH BUSI TERHADAP DAYA MESIN KIJANG INNOVA BENSIN - GINTING, TINUS (JTIK (Jurnal Teknik Informatika Kaputama), 2019)
The development of the automotive world experienced rapid development, and the most prominent development was in the ignition system. In this study will be discussed about the gasoline motor ignition system, especially the effect of spark plug gap on the power produced by the gasoline engine. The aim of research is to produce a good combustion process in the engine combustion chamber by determining the distance of the spark plug so that the sparks produced are perfect. The right spark plug gap will produce perfect combustion and the power produced will also be in accordance with the specifications of the engine. In order to maintain good spark plug work, it needs to be done in a maintenance manner to determine the extent of the effect of spark plug gap on the engine power of the gasoline motor. As for what will be examined in this study is the engine speed and engine power which is influenced by the distance of the spark plug to produce engine power on the gasoline motor. The method used in this study in the research is by using the direct method of conducting research in Cv. Prosperous motorbike. Materials used in research, one unit of Toyota Innova, with equipment measuring instruments and keys needed. In the study measurements were taken by measuring the distance of spark plug gap from 0.8 mm to the normal power, 0.6 mm the effect on power is not good because at high speed the fire jump is not large so the combustion is not perfect, and 1 mm the effect on the power The result is very low because the low and high speed sparks are unable to burn the fuel mixture. The results show differences in engine speed and power produced by the engine on a gasoline motor. To produce perfect engine power, it is necessary to do routine maintenance, especially the ignition system for spark plugs so that ignition and engine power are produced as stable as the specifications.